2022
DOI: 10.1111/basr.12251
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of mandatory corporate social responsibility expenditure: An empirical evidence from India

Abstract: The transition in governmental approach towards corporate social responsibility (CSR) from voluntary to mandatory has received much attention in the recent literature, mainly because the delegation of its role in social development has rarely been provided. In this context, the questions we raise are: Does mandatory CSR leads to higher expenditure? How does it affect business leaders' intrinsic motivation to spend on CSR? The case of India's section‐135 of Companies Act, 2013 shows that mandatory CSR has made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…[32] state that resource-based and stakeholder theories can be used in an integrated framework to explain managerial incentives that affect CSR. Consistency is found between the resource-based view and stakeholder theory [33]. Both theories can be considered interrelated to explain the determinants of the relationship between intellectual capital and CSR.…”
Section: Theoretical Frameworkmentioning
confidence: 85%
“…[32] state that resource-based and stakeholder theories can be used in an integrated framework to explain managerial incentives that affect CSR. Consistency is found between the resource-based view and stakeholder theory [33]. Both theories can be considered interrelated to explain the determinants of the relationship between intellectual capital and CSR.…”
Section: Theoretical Frameworkmentioning
confidence: 85%
“…For example, Chen et al found that the CSR performance pressure on firms caused by mandatory disclosure of CSR information may force firms to excessively increase their expenditures on CSR-related activities, leading to a sharp increase in their short-term operating costs, which in turn is detrimental to their economic performance [2]. Similarly, Gupta and Chakradhar found that the stock price of regulated firms decreases with the implementation of mandatory CSR policies [6,28]. In turn, the decrease in stock price level and economic performance may negatively affect the firm's cost of equity, financing efficiency, and therefore discourage activities such as R&D and investment, which may ultimately act as a disincentive to firm productivity.…”
Section: Theoretical Analysis and Hypothesismentioning
confidence: 99%
“…Compared to previous studies, this paper may make marginal contributions in the following three areas: First, although the disclosure of CSR reports is a growing trend worldwide, previous studies on the economic consequences of corporate CSR disclosure have mainly examined data from developed countries [5]. And studies have shown that the implementation of the same CSR policy in different countries may have diametrically opposite economic consequences due to reasons such as economic systems and cultural backgrounds [6,7]. As the largest developing country, China's unique socialist system has led its economy to take a very different path from that of Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Less able CEOs over or underinvest in an opportunistic way for personal benefit at shareholders' expense (Garcia-Sanchez & Martinez-Ferrero, 2019). CEOs may face pressure from institutional environments such as government regulations for CSR investments (Gupta & Chakradhar, 2022). Firms may suffer from possible misappropriation and misallocation of scarce resources (Garriga & Melé, 2004;Margolis & Walsh, 2003).…”
Section: The Mediation Effect Of Csr On the Relationship Between Loca...mentioning
confidence: 99%